Pengaruh Media Pembelajaran Quizizz Paper Mode terhadap Hasil Belajar pada Mata Pelajaran Informatika Siswa Fase E di SMA N 1 Sarolangun - Andini, Vina Fitri; Asmara, Delvi (TSAQOFAH, 2025)
This study is motivated by the low learning outcomes of students in Informatics subjects, partly due to the limited variety of learning media used. The purpose of this research is to determine the effect of using Quizizz learning media in Paper Mode on the learning outcomes of tenth-grade students at SMA N 1 Sarolangun. The method employed was quasi-experimental with a Nonequivalent Control Group Design. Data were collected through pretest and posttest assessments and analyzed using the Independent Samples t-Test. The analysis results show a tcount value of –4.529 with a significance value (Sig. 2-tailed) < 0.001, greater than the ttable value of 2.012 at the 5% significance level. Thus, H₀ is rejected and Hₐ is accepted, indicating a significant effect of using Quizizz Paper Mode on student learning outcomes. The study concludes that Quizizz Paper Mode is effective in improving student achievement in Informatics. The implications suggest that the use of interactive media adapted to classroom conditions can serve as an innovative alternative to enhance student engagement and learning outcomes.